Dinâmica e disponibilidade de fósforo em solos cultivados com cafeeiro em produção - Reis, Thiago Henrique Pereira (2009)
During many years coffee (Coffee arabica L.) plants have been considered low responsive to phosphorus fertilization. However, recent research data show that these plants demand high phosphorus quantity to fully develop their vegetative and reproductive systems. Aiming to know how phosphorus availability is influenced by annual P doses and how they may influence the future phosphorus fertilization management, this work was developed with the following objectives: (a) to quantify the labile, moderate-labile, low-labile and total P fractions associating them to coffee yield; (b) to quantify inorganic calcium, iron and aluminum P fractions associating them to soil mineralogy. For this purpose two experiments were analyzed in two coffee production areas: (1) in a typic dystrophic Red Latosol (Oxisol) located in an irrigated area - Planaltina, DF, with triple superphosphate annual fertilization of 0, 50, 100, 200 and 400 kg ha-1 P2O5 in randomized blocks with three replications; (2) in a typic dystrophic Red Argisol (Ultisol) located in an area without irrigation - Cabo Verde - south of Minas Gerais, in two production areas: one receiving 300 kg ha-1 P2O5, being 2/3 applied as simple superphosphate and 1/3 as magnesium thermophophate, and another with no P fertilization in the evaluated agricultural years, in randomized blocks with four replicates. Phosphorus fractions were determined in soil samples collected at three depths: 0-10, 10-20 and 20-40cm, according to Chang & Jackson (1957), Hedley et al. (1982) and Bowman (1989) methodologies. It was observed that the irrigated coffee plant responded to phosphorus fertilization, obtaining gains up to 138% of productivity with the application of 400 kg ha-1 P2O5 dosis. The leaves P content increased with soil P application doses and stabilized around 1.9 to 2.0 g kg-1. The soil P addition influenced the P fractions at all three depths studied. The bio-available P compartment showed to be highest soil P reservoir, although the estimated residual P showed substantial values at the 0-10cm depth. The P applied in the soil remains mainly linked to Al which is the main P form furnishing the nutrient to coffee plants. The inorganic P fractions presented the following sequence: P-Al > P-Fe > PCa.